PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPASISWA KELAS IV MI AL-MUHAJIRIN MENGGALA SAKTI KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Umi Kalsum; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Problems in this research is that result study student's IPA to be categorized still low to be becaused student student still difficulty in to accept lesson, active less student in to accept lesson, less teacher to involve it student in study and teacher only to use it lecture method and less student involved direct to to determine it self and the knowledge that to own it. From problemmer mentioned necessary be done Class Action Research ( PTK ) with Model implement Contextual Teaching and Learning ( CTL ) . this Research have go to to to level it result study class student IPA MI IV Al-Muhajirin Menggala Magic of White Soil with student's number many 20 student's people. this Research is done with 2 cycle, every cycle consist from 2 time meeting with 1 time repeating of daily. data Instrument collection to research this is teacher's observation sheet, student's observation sheet and result test study. the activity data analysiical-Result teacher to cycle meeting I first 57,14 % and second meeting to level become 64,28 %. To cycle meeting II first 89,28 % and second meeting to level become 96,42 %. Next the activity data analysiical-result student to cycle meeting I first 53,57 % and second meeting to level become 64,28 %. To cycle meeting II first 85,71 % and second meeting to level become 96,42 %. From this research result be obtained result study student to undergo leveling that is average result study student to base skor is 64,50 to level to cycle I become 66,75 to level again to cycle II 73,25 To completing study to base skor is 9 people ( 45% ) to level to cycle I become 12 people ( 60 % ) and to level again to cycle II become 20 people ( 100 % ). With such can to be concluded that to be applied Model Contexstual Teaching and Learning ( CTL ) can to level it result study class student IPA MI IV Al-Muhajirin Menggala Magic of White Soil.Key Word : Model Contextual Teaching and Learning ( CTL ), Result study IPA.